Notes on Early Land Plants Today. 56. Validation of Asterella sect. Wallichianae (Aytoniaceae, Marchantiophyta) - Long, David G.; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
Long (2005) presented an infrageneric classification of the genus Asterella Palisot de Beauvois (1805: 257) where five subgenera and four sections were recognized. Two of the sections were placed under subgen. Wallichianae Long (2001: 43), sect. Californicae Long (2005: 257) and sect. Wallichianae Long (2005: 257). However, since the latter section was not automatically defined as an autonym directly under the genus Asterella, it needed a Latin description which was missing. In order to be able to use the name in the forthcoming world checklist of Hornworts and Liverworts (Söderström et al., in prep.), the section is validated here. Note that a Latin description is no longer needed under the current ICN (McNeill et al. 2012).